Systemic mucormycosis caused by Rhizopus microsporus in a captive bottlenose dolphin - Lingling Chang (Wiley, 2021)
Abstract A 6‐year‐old female bottlenose dolphin (Tursiops truncatus) kept in dolphinarium died after a 3.5‐month period of lethargy and inappetence despite antibiotics and supportive care. At necropsy, gross findings included diffuse varying‐sized nodules in the lungs and scattered nodules throughout the heart, spleen, mesenteric and hilar lymph node and kidney. Microscopically, the lesions were characterised by disseminated fungal pyogranulomas with numerous intralesional Mucor‐like fungi. The fungi structures were demonstrated by Periodic acid‐Schiff and Gomori methenamine silver stain. Molecular analyses of the fungi were Rhizopus microsporus by PCR sequencing 18S ribosomal RNA gene. Ziehl–Neelsen stain failed to show acid‐fast bacterial infection. Based on pathological and molecular examination, systemic granulomatous mucormycosis was diagnosed. To our knowledge, this is the first reported case of systemic mucormycosis caused by Rhizopus microsporus in bottlenose dolphin.